Prevalence of the special needs of patients served in a type III CEO of a reference hospital in Brazil (Research, Society and Development, 2021)
The aim of this study was to determine the prevalence of Patients with Special Needs seen at the pediatric outpatient clinic of a type III CEO.Method: Descriptive cross-sectional study carried out by surveying 1,384 clinical records of patients from 0 to 19 years of age, with confirmed diagnoses of some special need and attended from June to September 2018.  Information collected from medical records such as: the registration number, sex, age, origin, the type of special needs and the history of caries experience. Then, the classification was applied according to the diagnosed pathology, elaborated by Santos & Haddad. Results: Most patients were male (58.2%) and lived in the Metropolitan Region of Recife (51.4%). Regarding special needs, it was found that the highest percentages correspond to patients with Congenital Defects (27.4%), Chronic Systemic Diseases (21.1%), Special Physiological States (15.2%), Physical Defects (14, 7%), Sensory and Audio-communication Defects (8.5%), Behavioral Deviations (4.8%), Intelligence Deviations (4.3%), Endocrine-Metabolic Diseases (3.6%) and Deviations Psychic (0.2%).